2016
DOI: 10.3390/ijms17101716
|View full text |Cite
|
Sign up to set email alerts
|

Auraptene and Other Prenyloxyphenylpropanoids Suppress Microglial Activation and Dopaminergic Neuronal Cell Death in a Lipopolysaccharide-Induced Model of Parkinson’s Disease

Abstract: In patients with Parkinson’s disease (PD), hyperactivated inflammation in the brain, particularly microglial hyperactivation in the substantia nigra (SN), is reported to be one of the triggers for the delayed loss of dopaminergic neurons and sequential motor functional impairments. We previously reported that (1) auraptene (AUR), a natural prenyloxycoumain, suppressed inflammatory responses including the hyperactivation of microglia in the ischemic brain and inflamed brain, thereby inhibiting neuronal cell dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…A number of recent studies showed that glial cells might be a cellular target for therapeutic approaches to treat several neurodegenerative diseases and neurological disorders, because glial cells, especially astrocytes, serve as key elements in the formation, maintenance, and refinement of synapses [13][14][15]. In our earlier studies regarding the neuroprotective ability of AUR, we revealed that (1) AUR has the ability to suppress inflammatory responses in vivo, namely, hyperactivation of microglia/astrocytes, and over-expression of inflammatory factors by astrocytes, in some mouse models of brain disorders; thus, resulting in the suppression of neuronal death in the hippocampus [3][4][5][6]; and (2) AUR has the ability to induce GDNF expression in C6 cells [9] in vitro. This series of our studies thus suggested that the site of neuroprotective ability of AUR might be astrocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of recent studies showed that glial cells might be a cellular target for therapeutic approaches to treat several neurodegenerative diseases and neurological disorders, because glial cells, especially astrocytes, serve as key elements in the formation, maintenance, and refinement of synapses [13][14][15]. In our earlier studies regarding the neuroprotective ability of AUR, we revealed that (1) AUR has the ability to suppress inflammatory responses in vivo, namely, hyperactivation of microglia/astrocytes, and over-expression of inflammatory factors by astrocytes, in some mouse models of brain disorders; thus, resulting in the suppression of neuronal death in the hippocampus [3][4][5][6]; and (2) AUR has the ability to induce GDNF expression in C6 cells [9] in vitro. This series of our studies thus suggested that the site of neuroprotective ability of AUR might be astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Auraptene (7-geranyloxycoumarin; AUR), a citrus coumarin derivative, has been revealed to possess valuable pharmacological properties, including anti-carcinogenic, anti-inflammatory, anti-oxidative, anti-helicobacter, anti-diabetic, anti-hypertensive [1], and neuroprotective ones [2]. We previously demonstrated that AUR exerts anti-inflammatory effects in not only peripheral organs but also the brain, as found from studies using a mouse model of global cerebral ischemia [3,4] and lipopolysaccharide (LPS)-induced systemic inflammation [5,6]. In the process of studying about the neuroprotective effects of AUR, we clarified that (1) AUR has the ability to phosphorylate (i.e., activate) extracellular signal-related kinase (ERK), a component of mitogen-activated protein kinase (MAPK), in rat primary cortical neurons [7]; (2) In the rat pheochromocytoma cell line (PC12 cells), AUR can cause phosphorylation of ERK and of cAMP response element-binding protein (CREB), a downstream target of ERK and a crucial transcription factor for neuronal plasticity and long-term potentiation (LTP) in the brain [8]; and (3) AUR phosphorylates ERK and CREB in rat C6 glioma cells [9].…”
Section: Introductionmentioning
confidence: 99%
“…Prenyl oxycumarins are a category of coumarins belonging to the family of Rutaceae and Apiaceae 7 . The most abundant prenyl oxycumarin in the nature is granyl oxycoumarin or Auraptene (AUR), which is well known today for its many pharmaceutical properties including high anti-cancer, antimicrobial, anti-fungal, anti-inflammatory, antioxidant, antibacterial for the tooth 8 liver and nerve protective, and anti-hypertension properties 9,10 . Several studies have reported that Auraptene has the potential of apoptosis induction in breast and gastric cancer cells.…”
mentioning
confidence: 99%
“…Also, citrus contains antioxidative compounds such as flavonoids (Green et al, 2011), which act by neutralizing the oxidizing free radicals (Abdel Moneim, 2014). Moreover, Okuyama et al (2016) stated that auraptene (AUR), citrus peel component, exerted suppressive effects on astrocyte activation and neuronal cell death in the brain of a lipopolysaccharide -injected inflammation model. Furthermore, Okuyama et al (2018) found that AUR and naringin (NGI) significantly suppressed tau phosphorylation in the hippocampus of hyperglycemic rats, and they referred this to its antioxidant properties.…”
Section: Discussionmentioning
confidence: 99%